A Mutant Era GTPase Suppresses Phenotypes Caused by Loss of Highly Conserved YbeY Protein in Escherichia coli - Babu, Vignesh M. P.; Sankari, Siva; Ghosal, Anubrata; Walker, Graham C. (Frontiers in Microbiology, 2022)
Ribosome assembly is a complex fundamental cellular process that involves assembling multiple ribosomal proteins and several ribosomal RNA species in a highly coordinated yet flexible and resilient manner. The highly conserved YbeY protein is a single-strand specific endoribonuclease, important for ribosome assembly, 16S rRNA processing, and ribosome quality control. In Escherichia coli, ybeY deletion results in pleiotropic phenotypes including slow growth, temperature sensitivity, accumulation of precursors of 16S rRNA, and impaired formation of fully assembled 70S subunits. Era, an essential highly conserved GTPase protein, interacts with many ribosomal proteins, and its depletion results in ribosome assembly defects. YbeY has been shown to interact with Era together with ribosomal protein S11. In this study, we have analyzed a suppressor mutation, era(T99I), that can partially suppress a subset of the multiple phenotypes of ybeY deletion. The era(T99I) allele was able to improve 16S rRNA processing and ribosome assembly at 37°C. However, it failed to suppress the temperature sensitivity and did not improve 16S rRNA stability. The era(T99I) allele was also unable to improve the 16S rRNA processing defects caused by the loss of ribosome maturation factors. We also show that era(T99I) increases the GroEL levels in the 30S ribosome fractions independent of YbeY. We propose that the mechanism of suppression is that the changes in Era’s structure caused by the era(T99I) mutation affect its GTP/GDP cycle in a way that increases the half-life of RNA binding to Era, thereby facilitating alternative processing of the 16S RNA precursor. Taken together, this study offers insights into the role of Era and YbeY in ribosome assembly and 16S rRNA processing events.